KREATIVITAS ANAK SEBAGAI PROSES PEMBENTUKAN KARAKTER SEJATI - Pitersina Ch Lumamuly (IAKN Ambon, 2018)
Creative as one character value is very precise because it will actively make a person not passive. His soul is always restless (in a positive sense), his mind is constantly evolving and always doing activities within the framework of searching for new things that will later benefit him but others. Of course, in sharpening the creativity of children need others especially educators and parents who are able to do, learn, apply (Do, Learn, Apply) then our knowledge, understanding and experience will increase from the activities we do every day.